Penerapan Metode Bermain Peran untuk Meningkatkan Hasil Belajar Keberagaman Budaya pada Siswa Kelas IV SD Negeri 080 Panyanbungan - Nadilah, Nadilah; Hanida, Rahmi Seri; Siregar, Ali Yusro (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study aims to determine the application of role-playing methods to improve learning outcomes of cultural diversity in grade IV students. This study was conducted at SD Negeri 080 Panyabungan. The research method used is the classroom action research method (CAR) with a posttest research design. Sampling was carried out using the total sampling technique. The sample of this study amounted to 30 students. The instruments in collecting this data were observation and tests. Where it can be seen from the increase in the average learning outcomes of students in cycle I of 72.6 with the number of students who achieved KKM 22 students (73%) and the number of students who did not achieve KKM 8 students (27%) and increased in cycle II with an average learning outcome of 83.3 with the number of students who achieved KKM 28 students (93.3%) and the number of students who did not achieve KKM 2 students (7%) and increased by 10.7%. This means that efforts to improve student learning outcomes using the application of the Role Playing method to improve the learning outcomes of cultural diversity of grade IV students of SD Negeri 080 Panyabungan, Panyabungan District can be said to improve student learning outcomes effectively.